INCREASING INTEREST AND MATHEMATICAL LEARNING OUTCOME IN MATHEMATIC OF TRIGONOMETRY BASIC COMPETENCE (KD) BY USING RECIPROCAL TEACHING MODEL FOR STUDENTS OF CLASS X MIPA 4 SMA NEGERI 5 MAGELANG IN THE EVEN SEMESTER OF ACADEMIC YEAR 2017/2018 - Endang Kristiyani (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This type of research was classroom action research that aims to increase students' interest and learning outcomes in Mathematics of SMA Negeri 5 Magelang through Reciprocal Teaching Model. This study involved 26 students of class X MIPA 4, which were conducted in two cycles and each cycle consisted of 3 meetings. In Cycle I, each group was a large group consisting of 6-7 members and in Cycle II, each group was a small group consisting of 3-4 members. In cycle I, the one who has medium capability in Mathematics was selected as a leader to present the material, while in cycle II, the one who possess the best capability in Mathematics was selected as a leader to present the material. In each cycle there were four stages; planning, implementation, observation and reflection. Data regarding on learning interest was taken from the observation sheet filled in by students. Then, learning outcome data was taken through daily tests at the end of each cycle. Data were analyzed by using comparative descriptive and qualitative descriptive techniques. The results of the study showed that there was a significant increase in learning interest and student learning outcomes after applying Reciprocal Teaching Model. The improved learning outcomes were indicated by daily test scores increase in the initial conditions, cycle I and cycle II. The percentage of students with high interest categories in the initial condition was 7.69%, increasing to 30.77% in cycle II. The percentage of students with interest was very high, that was 0% in the initial condition increase to 57.69% in cycle II. The improved learning outcome was indicated by daily test scores increase in the initial conditions, cycle I and cycle II. In the initial condition, the average score of 41 students increased to 86 in cycle II. The classical learning completeness also experienced a significant increase, from 26.92% in the initial conditions to 96.15% in the final condition. Reciprocal Teaching Model provides benefits for improving student understanding and quality of learning.